The Effect Provision of Moringa Oliefera Leaf Extract on the Event of Hypertension in the work Area Mata Health Center of Kendari City - Juharia, Cici; Supodo, Timbul; Akbar Torontju, Sultan (Waluya The International Science of Health Journal, 2023)
Introduction: The spread of hypertension in the world is a challenge in efforts to improve public health status. Preliminary studies were conducted on 10 patients with hypertension in the working area of the Mata Health Center, the results showed that the majority of hypertension sufferers were caused by genetics and lifestyle. Excessive sodium consumption and lack of activity due to the pandemic make them more often at home and often consume junk food and fast food. This attracted researchers to research the Effect of Giving Moringa Leaf Extract (Moringa oliefera) on the Incidence of Hypertension in the Working Area of the Mata Health Center of Kendari City. Method: Quantitative research with a quasi-experimental research design, namely the one-group pre-test-post-test-control design approach. The population is 580 people and the sample is 137 people with hypertension, some of whom are outpatients. Data analysis using the Wilcoxon test with a significance level of α = 0,05. Result: Before being given treatment (Pretest) namely Moringa leaf extract (Moringa oleifera I) the average blood pressure was 142,05 while after treatment (Posttest) it was 171,45. Conclusion: There is an effect of giving Moringa leaf extract (Moringa oleifera) on the incidence of hypertension in the working area of the Mata Health Center in Kendari City.